Solusi Desain Meja Tamu Lipat Bagi Hunian Minimalis Dengan Keterbatasan Ruang - Aji Nugroho, Muhammad Wahyu; Agus Susila, Dwi; Drajad Wibowo (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The limited space in modern residences, especially in urban areas with high population density, demands innovative solutions in the design of efficient and multifunctional furniture. This article aims to design a foldable coffee table that meets both aesthetic and functional needs while optimizing space usage in limited dwellings. The design process begins with data collection through user needs surveys, identification of common challenges in arranging small spaces, and ergonomic analysis. Material selection is focused on lightweight, durable, and environmentally friendly materials, such as high-quality, long-lasting teak wood and corrosion-resistant metal. The folding mechanism used employs modern hinges that are easy to operate and highly durable to ensure the safety and comfort of users. Additionally, a minimalist design with simple aesthetic elements was chosen so that the table can blend with various interior styles. Observations indicate that this table effectively saves space when folded, without compromising its stability and durability when used as a coffee table. The design methodology includes identifying user needs, functional analysis, and exploration of practical folding mechanisms and materials. This article contributes to creating innovative furniture solutions that are relevant to the needs of urban communities. By emphasizing ergonomic, flexible, and environmentally friendly design principles this foldable coffee table is expected to become an ideal alternative for residents of houses or apartments with limited space, while supporting a practical and efficient modern lifestyle.